2009
DOI: 10.1161/circulationaha.108.803528
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Everolimus-Eluting and Paclitaxel-Eluting Stents

Abstract: Background-In the prospective randomized Clinical Evaluation of the Xience V Everolimus Eluting Coronary Stent System in the Treatment of Patients with de novo Native Coronary Artery Lesions (SPIRIT) III trial, an everolimus-eluting stent (EES) compared with a widely used paclitaxel-eluting stent (PES) resulted in a statistically significant reduction in angiographic in-segment late loss at 8 months and noninferior rates of target vessel failure (cardiac death, myocardial infarction, or target vessel revascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(82 citation statements)
references
References 16 publications
2
77
0
3
Order By: Relevance
“…Newer DES (generation 3 DES) may need DAPT absolutely for only 3-6 months. 49 There are a number of on-going trials comparing short duration (3 months) versus standard duration (12 months) of DAPT administration. 50 4.…”
Section: Developments In Antiplatelet Therapymentioning
confidence: 99%
“…Newer DES (generation 3 DES) may need DAPT absolutely for only 3-6 months. 49 There are a number of on-going trials comparing short duration (3 months) versus standard duration (12 months) of DAPT administration. 50 4.…”
Section: Developments In Antiplatelet Therapymentioning
confidence: 99%
“…[8][9][10][11][12] But the study populations of most regulatory trials differ substantially from the patients treated in a 'real world scenario'. This discrepancy is underlined by the different rates of stent thrombosis in low-risk patients (as included in many regulatory trials) vs. high-risk patients and/or patients treated with DES in offlabel scenarios.…”
Section: Do We Need Randomised Post-marketing Studies In a 'Real Worlmentioning
confidence: 99%
“…Pivotal clinical trials have demonstrated the safety and efficacy of both stents. [8][9][10][11][12] The positive clinical results may reflect superior drug characteristics, polymer morphology, 13,14 and biocompatibility, [15][16][17] which may account for a better endothelialisation compared with older-generation DES. 18 When we started the present study no data from prospective randomised head-to-head comparisons between these two DES in a real-world scenario were available.…”
mentioning
confidence: 99%
“…It is the Everolimus is an antiproliferative agent primarily directed at cancer cells, but it is useful in other therapeutic domains as well, in particular for patients with coronary artery disease. A cobalt-chromium stent eluting everolimus was found to be more effective than a paclitaxeleluting stent, with fewer major adverse cardiac events [30].…”
Section: Novel Approved Np Drugs and Promising Clinical Candidatesmentioning
confidence: 93%